Immunomodulation induced by central nervous system‐related peptides as a therapeutic strategy for neurodegenerative disorders - María Laura Palumbo; Alejandro David Moroni; Sofía Quiroga; María Micaela Castro; Adriana Laura Burgueño; Ana María Genaro (Wiley, 2021)
Abstract Neurodegenerative diseases (NDD) are disorders characterized by the progressive loss of neurons affecting motor, sensory, and/or cognitive functions. The incidence of these diseases is increasing and has a great impact due to their high morbidity and mortality. Unfortunately, current therapeutic strategies only temporarily improve the patients' quality of life but are insufficient for completely alleviating the symptoms. An interaction between the immune system and the central nervous system (CNS) is widely associated with neuronal damage in NDD. Usually, immune cell infiltration has been identified with inflammation and is considered harmful to the injured CNS. However, the immune system has a crucial role in the protection and regeneration of the injured CNS. Nowadays, there is a consensus that deregulation of immune homeostasis may represent one of the key initial steps in NDD. Dr. Michal Schwartz originally conceived the concept of "protective autoimmunity" (PA) as a well‐controlled peripheral inflammatory reaction after injury, essential for neuroprotection and regeneration. Several studies suggested that immunizing with a weaker version of the neural self‐antigen would generate PA without degenerative autoimmunity. The development of CNS‐related peptides with immunomodulatory neuroprotective effect led to important research to evaluate their use in chronic and acute NDD. In this review, we refer to the role of PA and the potential applications of active immunization as a therapeutic option for NDD treatment. In particular, we focus on the experimental and clinical promissory findings for CNS‐related peptides with beneficial immunomodulatory effects.